Pengaruh Model Project Based Learning (PjBL) Bermuatan SDGs Terhadap Kemampuan Pemecahan Masalah Siswa Pada Materi Perubahan Iklim - Dicky Armanda; Kartika Manalu (Jayapangus Press, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model containing Sustainable Development Goals (SDGs) on students' problem-solving abilities in climate change material. The main problem of this study is the low ability of students to plan and evaluate solutions to environmental problems, due to the dominance of conventional approaches in the classroom. The method used is a quasi-experimental with Pretest-Postest Control Group Design for class X students of MAN 2 Deli Serdang. Data on problem-solving abilities were collected through essay tests based on Polya indicators and analyzed using the One-Way Anova test. The results showed that there was a significant difference between the experimental class and the control class (F count 108.280; Sig. <0.001). Students in the experimental class who implemented PjBL containing SDGs achieved significantly higher achievements in all problem-solving indicators than the control class, especially in the stages of planning solutions, implementing plans, and reviewing results. This proves that the SDGs-based PjBL model does not only function as a method variation, but is a transformative pedagogical intervention that effectively bridges the gap between academic theory and students' practical skills in synthesizing climate change mitigation solutions in a concrete and logical manner.